The crucial role of high school management in facilitating e-portfolio implementation in classrooms - Modise, Mpho-Entle Puleng; Majola, Xolani Moffat; Kotoka, Jonas Kwadzo (Journal of Education and e-Learning Research, 2025)
Rapid development of information communication technologies (ICTs) has enabled online technology to support flexible teaching and learning approaches in various contexts, including high schools. As a result, e-portfolios used in online and blended learning environments can be effectively implemented in high schools. This study emphasizes the central role of high school managers in integrating educational technology in schools to promote e-portfolios. Using a qualitative research approach and the Technology Adoption Model (TAM), data were collected through an online questionnaire. Thematic analysis was employed to analyze the open-ended questions, while descriptive statistics were used for the closed-ended questions. The findings indicate that members of school management can act as catalysts for teachers and learners to integrate technology in the classroom, thereby facilitating and supporting the implementation of this approach in schools. However, the study also found that members of school management are often neglected during training offered during technology implementation. This neglect results in the central role players lacking the necessary understanding and appreciation for the application of educational technology in the classroom. Based on these findings, it is recommended to prioritize awareness, training, and preparation for ICT integration for high school management teams.